PELESTARIAN TRADISI PUKUL KENDI DUSUN GARUDA, KRUCIL, PROBOLINGGO - Faizah, Nur; Mariska, Refi; Rizki, Vita Vitriati (Kalam Nusantara Institute, 2024)
One of the cultures found in a local community is customs, which is a value system that applies until the end of life. Customs are binding but unwritten rules that have a function as rules that apply for generations. The custom of breaking a jug is a Hindu culture brought by Dewi Rengganis that is still preserved by the community. As happened in Garuda hamlet, Krucil village, Krucil sub-district, Probolinggo district, East Java. The custom of breaking the jug is carried out when a Krucil villager dies. The purpose of this study is to determine the benefits of implementing and preserving the tradition of breaking the jug for the people of Krucil village, which is still preserved and believed to eliminate bad luck for those who die. With the preservation of culture, it can play a role as a differentiator between regions and a source of pride for the Indonesian nation. The method used in this service is ABCD. The results of this study indicate that preserving the culture owned by the region is an obligation in order to improve the quality of life that is cultured and blend into the local wisdom itself, so that later our children and grandchildren will know the existence of culture. Diversity, if nurtured and preserved, can strengthen the sense of national unity and integrity, which can also be passed on to future generations.